DEVELOPING READING NARRATIVE TEXT MATERIALS FOR EIGHTH GRADERS OF JUNIOR HIGH SCHOOL IMPLEMENTED WITH CHARACTER BUILDING (Universitas Negeri Semarang, 2012)
Degradasi moral sangat berperan besar dalam perubahan tingkah laku siswa seperti yang ditunjukan oleh surat kabar dan media masa. Character building diperlukan untuk diimplementasikan dengan segera, akan tetapi tidak ada buku yang membahas tentang hal tersebut. Studi ini bertujuan untuk menemukan materi naratif teks yang dibutuhkan oleh siswa kelas VIII, mengembangkan materi naratif teks, dan menemukan keefektifan serta kesesuaian materi. Research desain dari studi ini ialah Research and Development. Subjek studi ialah 40 siswa SMP. Studi dilakukan dengan analisis, mengembangkan materi, validasi ahli, dan try out. Studi mkenunjukan bahwa siswa membutuhkan materi naratif teks berisikan character building. Temuan terakhir menunjukan bahwa materi sesuai diterapkan kepada siswa untuk mempelajari naratif teks dan poin dari character building di dalamnya.Moral degradation has impacted students’ behavior recently as it is also shown in mass media and in school. Character building need to be implemented in students’ learning activity, however, there is no book includes character building in it. This study intends to find out a narrative reading text materials needed by eighth graders, develop a narrative text reading text materials, and to find out the effectiveness and the appropriateness of the materials. The research design of this study is research and development. The subjects were 40 students of junior high school. The study was conducted by doing need analysis, developing materials, expert validation and try out. The research finding reveals that students need a set of narrative reading text materials which are implemented with character building. So the materials were developed based on the students’ need and the syllabus mapping. Some improvements were conducted in order to enclose the effectiveness and appropriateness of these materials. The last finding reveals that the materials suit on students of this stage as they learn narrative text well and learn some points of character building in it.